Peran Simulasi Sadari sebagai Upaya Meningkatkan Pengetahuan Remaja Putri akan Resiko Kanker Payudara - Andini Setyaningrum; Rizki Yulia Purwitaningtyas; Roshinta Sony Anggari (Akademi Kesehatan Rustida, 2021)
Knowledge of young women on health, especially the risk of breast cancer, can be said to be still lacking. This can be seen from the behavior that is not sensitive to abnormal symptoms that arise in the breast such as a lump. Breast self-examination (BSE) is one way of early detection of breast cancer risk that is easy to do. This study aims to determine the effect of BSE simulation on the level of knowledge of young women in a private high school (SMA) in the Banyuwangi area. The method used is Quasi Experimental with One Group Pre test and Post test design. Respondents in this study amounted to 44 high school students who were selected by purposive sampling technique. The results of the pre-test showed that before being given health education, most of the students' knowledge was sufficient (62.8%), while after the intervention (post-test) simulation, the students' knowledge was good (77.3%). The results of the analysis using the independent sample t-test showed a significant influence on the knowledge of high school students before and after the intervention with p value <0.05. The active role of the school together with health workers to continue to provide simulations of breast self-examination should continue to be improved and carried out on an ongoing basis. Thus, students will be more sensitive to abnormal changes in their bodies, especially those at risk of breast cancer.